2014
DOI: 10.1017/s0967199414000653
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitrification of immature bovine oocytes to the subsequentin vitrodevelopment and gene expression

Abstract: Immature bovine oocytes were vitrified using the cryotop method and their post-warming survivability and capability to undergo in vitro maturation, fertilization and subsequent embryonic development were evaluated. In addition throughout the embryonic 2-cell, 4-cell, morula and blastocyst stages, the expression of four developmentally important genes (Cx43, CDH1, DNMT1 and HSPA14) was analysed using the real-time polymerase chain reaction (PCR). Immature oocytes (n = 550) were randomly assigned to non-vitrifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…For each gene, cDNA dilution curves were generated and used to calculate the individual real-time PCR efficiencies by E = 10(–1/slope) – 1. Relative gene expression analysis was performed using the Relative Expression Software Tool (REST©) with the Pair Wise Fixed Reallocation Randomization Test© method (Pfaffl et al , 2002; Faheem et al , 2014) with the calculated E values introduced. The relative expression values (C t ) are presented as mean ± SEM.…”
Section: Methodsmentioning
confidence: 99%
“…For each gene, cDNA dilution curves were generated and used to calculate the individual real-time PCR efficiencies by E = 10(–1/slope) – 1. Relative gene expression analysis was performed using the Relative Expression Software Tool (REST©) with the Pair Wise Fixed Reallocation Randomization Test© method (Pfaffl et al , 2002; Faheem et al , 2014) with the calculated E values introduced. The relative expression values (C t ) are presented as mean ± SEM.…”
Section: Methodsmentioning
confidence: 99%
“…The membrane permeability of DMSO is lower than that of EG, probably because of the involvement of different aquaporin channels (Edashige, 2016 ). In Cryotop vitrification of bovine immature oocytes, the use of EG/PG‐based VS instead of EG/DMSO‐based VS resulted in a higher IVM outcome (90% vs. 76%), but a comparable blastocyst yield (10% vs. 14% per matured oocytes; Faheem et al, 2015 ). Recently, Somfai and Hirao ( 2021 ) reported that the replacement of DMSO with PG in protein‐free VS with a few additional modifications resulted in a statistically comparable blastocyst yield from post‐warmed bovine immature oocytes (12% vs. 8%).…”
Section: Application To Immature Oocytesmentioning
confidence: 99%
“…Data analysis was performed as described by Faheem et al (2014) and Pavani et al (2016) for embryos. For comparisons between genes, data from GV stage COC's collected during winter were used as a calibrator group for relative gene expression analysis.…”
Section: Methodsmentioning
confidence: 99%